Failing to Foresee the Updating of the Reference Point Leads to Time-Inconsistent Investment - Strub, Moris S.; Li, Duan (Operations Research, 2020)
In a dynamic setting, decision makers update their reference point as a function of previous decision and outcomes. In “Failing to Foresee the Updating of the Reference Point Leads to Time-Inconsistent Investment,” Strub and Li investigate the influence of reference point updating on decision making and in particular, address whether a decision maker foresees the updating of the reference point in the context of discrete time portfolio optimization. By deriving and comparing optimal trading strategies under various frameworks and reference point updating rules and then, simulating how typical investment behavior would look like in each setting, they come to the following conclusion: a loss-averse decision maker with a time-varying reference point exhibiting realistic investment behavior fails to foresee the future updating of the reference point, and this failure leads to time-inconsistent investment.